Rancang Bangun Aplikasi Augmented Reality untuk Pembelajaran Materi Bangun Ruang Sekolah Dasar - Antonio, Marcel; Bata, Julius (Jurnal Informatika Universitas Pamulang, 2023)
Geometry has emerged as a challenging topic in elementary mathematics due to its demand for solid cognitive capacities and spatial ability. Students struggle to understand geometry topics, particularly in solid space and three-dimensional objects. The students need help comprehending various three-dimensional shapes and understanding the formulas and definitions related to geometry. This paper aims to design and develop an application for learning solid space topics. The application provides explanations of solid space concepts, interactive exercises, and assessments to enhance students' understanding. The development process follows the ADDIE method, which includes Analysis, Design, Development, Implementation, and Evaluation. The application was evaluated by a mathematics teacher. We also conduct black-box testing. The result shows that all the functionality was valid and the application can be used by students. Future research will focus on implementing the application in actual mathematic classes and evaluating the impact on student learning.